The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1038/s41893-020-0532-7
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological limits to carbon capture and storage

Abstract: Post-combustion carbon capture and storage (CCS) is an important technology to reduce CO2 emissions from the electricity and industrial sectors. Despite the mounting concerns about global water scarcity and its impact on energy production, the potential hydrological consequences of large-scale CCS have not yet been explored. Here we simulate the impacts on water resources that would result from retrofitting global coal-fired power plants (CFPP) with four different CCS technologies. We find that 43% of global C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(36 citation statements)
references
References 63 publications
0
31
0
2
Order By: Relevance
“…We run WATNEEDS using baseline, 1.5 °C warmer, and 3 °C warmer precipitation and evaporation data while keeping the spatial extent of global croplands fixed to the MIRCA2000 dataset ( 39 )—the most updated dataset containing spatially explicit information of global croplands extent. WATNEEDS has been extensively used to assess CWR and IWR ( 9 , 10 , 14 , 57 , 58 ).…”
Section: Methodsmentioning
confidence: 99%
“…We run WATNEEDS using baseline, 1.5 °C warmer, and 3 °C warmer precipitation and evaporation data while keeping the spatial extent of global croplands fixed to the MIRCA2000 dataset ( 39 )—the most updated dataset containing spatially explicit information of global croplands extent. WATNEEDS has been extensively used to assess CWR and IWR ( 9 , 10 , 14 , 57 , 58 ).…”
Section: Methodsmentioning
confidence: 99%
“…This trade-off requires a thorough evaluation considering local boundary conditions, since water is a local resource and nowadays water scarcity is already widespread and perceived as a socio-economic risk to human activities. 192,193 4.1.3 Multi-functionality. With multi-functionality, we refer to the number of functions the product system provides.…”
Section: Synthesismentioning
confidence: 99%
“…soil quality change), although they exhibit high energy consumption 178,195 and could result in water issues in water scarce areas. 192 On the contrary, all other CDR technologies can exhibit substantial side effects including (i)LUC, food and water competition, 192,193 biodiversity and albedo change as well as ecosystem disturbances. 49 A full understanding of theseoften depending on regional, local, or even site-specific boundary conditions -is often missing, especially for EW and OF.…”
Section: Synthesismentioning
confidence: 99%
“…Water management is a relatively new topic in this area. A recent study has shown that water use is an important consideration in the implementation of CCS [105]. Lifecycle assessments of CCUS are also an urgent issue that should be studied further [106].…”
Section: Summary and Perspectivementioning
confidence: 99%